Alternative Splicing Generates Different Parkin Protein Isoforms: Evidences in Human, Rat, and Mouse Brain. (16th July 2014) - Scuderi, Soraya; La Cognata, Valentina; Drago, Filippo; Cavallaro, Sebastiano; D'Agata, Velia
Abstract : Parkinson protein 2, E3 ubiquitin protein ligase ( PARK2 ) gene mutations are the most frequent causes of autosomal recessive early onset Parkinson's disease and juvenile Parkinson disease. Parkin deficiency has also been linked to other human pathologies, for example, sporadic Parkinson disease, Alzheimer disease, autism, and cancer. PARK2 primary transcript undergoes an extensive alternative splicing, which enhances transcriptomic diversification. To date several PARK2 splice variants have been identified; however, the expression and distribution of parkin isoforms have not been deeply investigated yet. Here, the currently known PARK2 gene transcripts and relative predicted encoded proteins in human, rat, and mouse are reviewed. By analyzing the literature, we highlight the existing data showing the presence of multiple parkin isoforms in the brain. Their expression emerges from conflicting results regarding the electrophoretic mobility of the protein, but it is also assumed from discrepant observations on the cellular and tissue distribution of parkin. Although the characterization of each predicted isoforms is complex, since they often diverge only for few amino acids, analysis of their expression patterns in the brain might account for the different pathogenetic effects linked to PARK2 gene mutations.